WAYS OF USING DIGITAL TECHNOLOGIES IN BANKING ACTIVITIES - Shoakhmedova Nozima Khairullaevna; Yusupova Dilbar Mirabidovna (Scholar Express Journal, 2023)
This article covers digital banking technologies and their composition and elements. The scientific views of foreign and domestic scientists on banking technologies have been thoroughly studied, analyzed and author's opinions have been expressed. It also presents the banking technologies used today in the world's banks and reveals their unique features and advantages. In addition, scientifically based proposals have been developed for the effective use of banking technologies and further increase their efficiency
Keywords: Banking; banking technology; information technology; mobile banking